A role for antimetabolites in glaucoma tube surgery: current evidence and future directions. Issue 2 (March 2016) - Amoozgar, Behzad; Lin, Shan C.; Han, Ying; Kuo, Jane
Abstract : Purpose of review: Glaucoma is the leading cause of irreversible blindness worldwide. The main treatment modality for glaucoma is the reduction and control of the intraocular pressure (IOP). Glaucoma filtration surgery, including trabeculectomy and/or implantation of a glaucoma drainage device (GDD), is warranted if IOP remains medically uncontrolled. However, postoperative scarring remains a critical determinant of long-term bleb survival and IOP control after drainage surgery. Antimetabolites, such as mitomycin C and 5-fluorouracil, have been used for many years to increase survival time of filtration surgeries by preventing bleb fibrosis and scarring. The aim of this study is to provide an overview of: the current usage of these antimetabolites in GDD, the recent advancements of these antimetabolites in combination with other technologies, and the role of future antimetabolites. Recent findings: Mitomycin C and 5-fluorouracil have been used in GDD and trabeculectomy to prevent the exaggerated cellular reaction that leads to fibrosis. The adjunctive administration of these drugs intraoperatively and postoperatively has resulted in a lower rate of the hypertensive phase, and possibly a better long-term success rate in Ahmed valve surgeries. However, the application of these antimetabolites and their multiple-dosing applications are associated with nonspecific cytotoxicity and potentially severe complications such as bleb leak and conjunctival erosion over the tube. Recent studies are thus focusing on different medications, targeting new molecular pathways, and designing new delivery vehicles to minimize current antimetabolites side-effects and increase their efficacy. Promising results of these studies have led to development of new collaborative medications and advanced drug delivery systems for better modulation of GDD surgeries' predictable outcomes. Summary: The development of small molecule therapeutics, combination therapies, and innovative drug vehicles to prevent postsurgical fibrosis and achieve better surgical outcome in glaucoma filtration surgeries is promising.